Assessing Quality of Life and Social Support as Determinants of Life Satisfaction among Elderly in Kailali, Nepal - Sharma, Tilak Prasad (NUTA Journal, 2024)
The purpose of the research is to determine the association between social support quality of life and life satisfaction among elderly people living in Lamki Chuha Municipality, Kailali, Nepal 221 elderly people completed standard questionnaires utilizing a cross-sectional descriptive research method for data collection. The findings suggest that stronger social support perception causes better life satisfaction and quality of life results. In fact, concerned with perceived social support, it would seem that it played a significant role in the prediction of life quality and level of life satisfaction in the sample of older people which further underlines its importance for the quality of life. They have a very low level of education; they are mostly unemployed; and they have serious health complications. But even as they garner sufficient support, these issues can affect one’s perceived level of happiness and well-being. In turn, perceived support was proved to have a positive relation with ’life satisfaction’ and ’quality of life’ among the elderly population. Education and employment also played a significant role in the socioeconomic perspectives which are one of the quality of life influential factors in elderly people. Socio-economic aspects focusing on the improvement of social support and other spheres, to improve elderly people’s quality of life and life satisfaction, need to be also decentralized.